Heart Rate Predicts the Risk of New-Onset Peripheral Arterial Disease in a Community-Based Population in China - Gao Y (Dove Medical Press, 2021)
Yusi Gao, Fangfang Fan, Jia Jia, Yimeng Jiang, Danmei He, Zhongli Wu, Yong Huo, Jing Zhou, Yan Zhang Department of Cardiology, Peking University First Hospital, Beijing, People’s Republic of ChinaCorrespondence: Jing ZhouDepartment of Cardiology, Peking University First Hospital, No. 8 Xishiku Street, Xicheng District, Beijing, 100034, People’s Republic of ChinaTel +86-10-83575728Fax +86-10-66551383Email zhoujing123@yahoo.comIntroduction: Elevated heart rate is linked with poor prognosis and has been shown to accelerate the progress of atherosclerosis. However, the association between heart rate and new-onset PAD is unknown.Methods: A total of 3463 participants without PAD at baseline from a community-based cohort in Beijing were included and followed up for 2.3 years. PAD was defined as ankle–brachial index (ABI) ≤ 0.9. We used multivariate logistic regression models to investigate the association of heart rate and the risk of new-onset PAD.Results: Participants were 56.67 ± 8.54 years old, and 36.12% were men. The baseline ABI was 1.11 ± 0.08, and the incidence of new-onset PAD was 2.97%. Multivariate regression models, adjusted for sex, age, risk factor of atherosclerosis, medications, and baseline ABI, showed that heart rate was significantly associated with incidence of PAD (odds ratio [OR] = 1.22, 95% confidence interval [CI]: 1.03– 1.43, P = 0.020); every increase of 10 heart beats per minute (bpm) was associated with a 22% increase in the odds of developing new-onset PAD. Respondents in the higher-heart rate group (≥ 80 bpm) had an increased risk of new-onset PAD, compared with those in the lower-heart rate group (< 80 bpm) (OR = 1.73, 95% CI: 1.14– 2.63, P = 0.010). Subgroup analyses revealed no significant heterogeneity among the analyzed subgroups.Conclusion: Elevated heart rate was independently associated with the risk of new-onset PAD in a community-based population in Beijing. Heart rate management should be considered for the purpose of PAD prevention.Keywords: cohort studies, heart rate, peripheral arterial disease, ankle–brachial index